KINERJA KEPALA SEKOLAH DAN KINERJA MENGAJAR GURU DALAM PENINGKATAN MUTU SEKOLAH DASAR NEGERI DI KECAMATAN KOTA TANGERANG - Herayati Herayati (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
This study aims to determine the effect of principal performance (X1) and teacher performance (X2) on school quality (Y). The method used in this research is descriptive method with a quantitative approach with the study population consisting of 85 public elementary schools in Tangerang district. The total sample of 46 schools was taken based on proportionate stratified random sampling from all public elementary schools in the Tangerang city district to obtain data on school quality. The results of the descriptive analysis show that the school quality variable gets a score of 3.70 which is in the high category. This means that the quality of public elementary schools in the sub-district of Tangerang city is good. The dimension that gets the highest score is outcame at the first level, then the second input, the third enhanced process, and the last ranked output. Meanwhile, the school principal's performance variable obtained a score of 4.32 and was in the very high category. This means that the performance of school principals in the Tangerang sub-district has been very good. The dimension that gets the highest score is initiative at the first level, then the second is quality of work and capability, the third is improved promptness, and the last is communication. Then, the results of data processing on the teacher's teaching performance variable obtained a score of 4.59 and were in the very high category. This means that the teaching performance of teachers in the district of Tangerang city is very good. The dimension that gets the highest score is planning at the first level, then the second implementation, the final enhanced assessment.